2018
DOI: 10.37358/mp.18.4.5056
|View full text |Cite
|
Sign up to set email alerts
|

Fine Details Obtained by 3D Printing and Using Polymers

Abstract: The three-dimensional printing is a manufacturing method involving the addition of materials by using certain principles valid in printing techniques. There are various techniques of a three-dimensional printing method and the most of them could be applied inclusively to generate objects of polymers. The objective of the research presented in this paper was to analyze the capabilities of 3D printing process or equipment of generating fine details and to identify a way of evaluating these capabilities when usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The hypothesis that the accuracy of making areas with intersections in the form of sharp vertices could be improved if the thickness of the sample were large was still considered. Previously obtained results in the case of profiles generated on a plate had confirmed that areas characterized by intersection angles with sizes below a certain limit would no longer be able to be materialized by 3D printing, which will affect some dimensions of the produced parts [28]. Such a result could be even more obvious if the areas with sharp angles were not supported by a plate to which they were attached (Figure 1a).…”
Section: Hypothesesmentioning
confidence: 81%
See 1 more Smart Citation
“…The hypothesis that the accuracy of making areas with intersections in the form of sharp vertices could be improved if the thickness of the sample were large was still considered. Previously obtained results in the case of profiles generated on a plate had confirmed that areas characterized by intersection angles with sizes below a certain limit would no longer be able to be materialized by 3D printing, which will affect some dimensions of the produced parts [28]. Such a result could be even more obvious if the areas with sharp angles were not supported by a plate to which they were attached (Figure 1a).…”
Section: Hypothesesmentioning
confidence: 81%
“…Another group of researchers aimed to identify different shapes of parts that could be used to test the ability of additive manufacturing processes to produce certain details of the part [28,29] accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have led to the development of new techniques for treating silicone compounds in order to increase their consistency and resistance over time, as well as to improve their chemical stability. The coating of the prostheses are made up of three-dimensional silicone elastomers [7] with high mechanical strength that protects the silicone gel characterized by a variable cross-linking level and mechanical particularities strongly influenced by the degree of polymerization [8,9]. The consistency of the material increases in direct proportion to the number of dimethylsiloxane units within the polymers, affecting the physical properties of silicone [10].…”
mentioning
confidence: 99%